Impact of Iron Deficiency Anemia on the Occurrence of Febrile Seizures in Pediatrics - Safa’a Dakhel AbdulHassan (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Febrile seizures are the most common neurological disorder in children, and iron deficiency anemia is the most prevalent nutritional deficiency worldwide. Specific Background: Iron is essential for oxygen transport, brain metabolism, and neurotransmitter synthesis, and low iron status may reduce the seizure threshold in young children. Knowledge Gap: Previous studies have reported inconsistent findings regarding the relationship between iron deficiency anemia and febrile seizures. Aims: This study investigated the prevalence of iron deficiency anemia among children with febrile seizures and examined the association between iron deficiency anemia and febrile seizure occurrence. Results: A case-control study was conducted among 336 pediatric patients. Iron deficiency anemia was identified in 42.9% of participants, while 32.1% experienced febrile seizures. Among children with iron deficiency anemia, 41.7% had febrile seizures compared with 25.0% of those without anemia. The association was statistically significant (p = 0.032), and the odds ratio of 2.14 indicated that children with iron deficiency anemia were more than twice as likely to develop febrile seizures. The highest frequency of febrile seizures occurred in children aged 12–36 months, and lower hemoglobin and ferritin levels were observed in the febrile seizure group. Novelty: This study provides additional evidence from pediatric patients in Diwaniyah City supporting iron deficiency anemia as a significant and modifiable risk factor for febrile seizures. Implications: Routine screening and early treatment of iron deficiency anemia may help reduce the occurrence of febrile seizures in children. Highlights: • Children with iron deficiency anemia had a twofold higher likelihood of febrile seizures.• The 12–36 month age group showed the highest proportion of seizure cases.• Lower hemoglobin and ferritin levels were observed among affected pediatric patients. Keywords: Iron Deficiency Anemia, Febrile Seizures, Pediatric Patients, Hemoglobin, Ferritin